Penguatan Partisipatif dalam Penanganan Kawasan Permukiman Kumuh di Kelurahan Purirano Kota Kendari: Participatory Strengthening in Handling Slum Residential Areas in Purirano Sub-district, Kendari City - Widayati, Weka; Sawaludin, Sawaludin; Indriasary, Anita; Aulia, Weko Indira Romanti; Rahim, Saban (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Slum areas are currently of concern to the government, where the risk of slum areas can cause a decline in environmental and community health. Slum areas are settlements that are uninhabitable because there are building irregularities, building density conditions, building quality and a network of facilities and infrastructure that do not meet technical requirements. The aim of this activity is to identify and map slum areas and carry out socialization on the management of slum areas in Purirano Village, Kendari City. The method used in this activity is surveying and identifying slum areas and overlaying maps as well as conducting outreach to the government and community. The results of survey activities and identification of slum areas in Purirano sub-district are spread across the RT1, RT2, RT4, RT5, RT6 and RT7 areas which are caused by inadequate sanitation conditions, damaged drainage, damaged rubbish dumps and scattered residential rubbish and building conditions. inadequate house. Socialization for participatory strengthening to the government and community, namely the importance of coordination and collaboration in identifying slum area problems and planning appropriate solutions, as well as the need for an active role from the community in reporting problems, organizing improvement activities, and participating in handling slum areas. The implementation of handling slum areas in the Purirano sub-district is repairing and revamping waste disposal sites (TPS) in RT2 as part of a waste infrastructure development prototype which can be an example for improving environmental and sanitation infrastructure.